Physical properties of tofu gel probed by water translational/rotational dynamics. (April 2018) - Kawaguchi, Tsubasa; Kita, Rio; Shinyashiki, Naoki; Yagihara, Shin; Fukuzaki, Minoru
Abstract: The dynamic behavior of water molecules in tofu gels is observed using dielectric spectroscopy (DS) and pulsed field gradient nuclear magnetic resonance (PFG-NMR) methods. The breaking stress of tofu gels are dependent on the heating time, which affects the water structures characterized by the dielectric relaxation time, τ . On the other hand, the inhomogeneity of the gel structures decreases with increasing coagulant concentration was reflected as decreasing of the dielectric broadening parameter, β, that related for a fluctuation of the dynamic water structure. In addition, a decrease in the translational diffusion coefficient of water molecules is obtained with increasing coagulant concentration suggesting a reduction of the free space for the diffusional motion of water molecules. Negative correlations between the broadening parameter, β, and the inverse of diffusion coefficient, 1/D, are found in tofu gels and soymilk with distinct correlation coefficients of −0.95 and −0.87, respectively. These results suggest that water dynamics analysis and complementary analysis using DS and PFG-NMR measuring techniques can be an effective tool to evaluate food gel physical properties. Further these technique could also explain the molecular mechanisms of gel and liquid structures and properties via dynamic water structures. Graphical abstract: Image 1 Highlights: Free water content was determined by noninvasive dielectric measurements for tofu. Relaxation time, τ, for free water in tofu increased with the heating time. Fluctuation of water molecules in tofu increased with the coagulant concentration. Diffusion of water molecules reflects fluctuations of small scale reorientation in tofu.